GANGGUAN EMOSIONAL PADA PELAJAR SMK DI DEPOK SAAT MASA PANDEMI COVID-19 - Sinta Aulia Fikriah; Rahma Aliyya Kurnianingrum; Luthfiyyah Zahra; Dwi Setiowati (Politeknik Negeri Sriwijaya, 2022)
During the Covid-19 pandemic, emotional difficulties among SMK students in Depok became a big issue that must be of particular care to all pasties. This is related to mental health in adolescents, because mental health in adolescents is an important factor in the physical and psychological development of adolescents. The new culture of studying at home without a teacher or direct companion is a problem in and of itself, putting strain on SMK pupils and causing emotional issues (GE). This study intends to discover how emotional illnesses manifest themselves among Depok vocational students during the Covid-19 pandemic. By doing a literature review and descriptive data analysis with univariate analysis, this research is descriptive qualitative. A sample of 55 students in Depok was taken purposively. The results showed that 49% of vocational students in Depok experienced emotional disorders, this was because students felt uncomfortable, stressed, and depressed when learning online and often experienced headaches and fears when learning online, from 55 respondents 71% were women so that the most vulnerable to experiencing emotional disorders are adolescent girls due to stress, headaches, depression, lack of confidence, and discomfort in online learning.